Designing Comics of Joko Sambang Folklore - Lia Nirawati S1 (Saraswati)
Folktale is a part of folklore, which is defined as a form of storytelling that basically spread orally and handed down for generations among the supporters community traditionally. While folklore can be subdivided into three categories, namely: myths, legends and fairy tales. Folklore usually tells about the ancestors or the origins of a place in Indonesia. Folklore is full of moral values and wisdom that can be a means of communication to teach life values to children. The rapid development of technology makes folklore increasingly marginalized, so it is impact to many kids that do not know the folklore in Indonesia. One of the stories that should be retold to the children is the folklore of Joko Sambang. This folklore is a story that comes from Pasuruan, East Java. The values contained are like heroism and nationalism that really strong. The media which is fit to the children is a comic book. Comic is an effective media because it is the combination between image and text, so the children can easily get the message that will be delivered in the comic. With the designing this comic of Joko Sambang, is expected to foster the spirit of nationalism as early as possible in children and help to preserve the local culture especially the folklore oral culture through the media of comic.Keywords: Comic, Folklore, Pasuruan, Children, Joko Sambang